Helicobacter pylori in ice cream and its control using mastic gum essential oil - Saad, Nagah Mohamed; El-Zamkan, Mona Ahmed (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study aimed at assessing the prevalence of Helicobacter spp. in ice cream sold at Qena city (Egypt) with special reference to H. pylori, and to study the antimicrobial effect of mastic gum essential oil on H. pylori. Materials and methods: A total of 60 small and large scale ice cream samples (30 each) were investigated for the presence of Helicobacter spp. Then, the essential oil of mastic gum was added to lab prepared ice cream inoculated with H. pylori isolate in a count of Log6 using 2 concentrations of 0.8 and 1.6% and one group was kept as a control group. Each group was subdivided into 2 sub-groups; one was kept at -5°C and another one was kept at -20°C. Results: Helicobacter spp. could be isolated from 11.7%, while, H. pylori could be found in 3.3% of the total examined ice cream samples. Regarding the anti-Helicobacter pylori effect of mastic gum essential oil added to lab prepared ice cream, in samples kept at -5°C it was found that after hardening the count fall into Log5 in both control and 0.8% groups and log4 in 1.6% essential mastic oil concentration. Reduction in H. pylori at the first week and third day of storage reached 100% where H. pylori couldnt be counted or isolated from both 0.8 and 1.6% concentrations, respectively. While in ice cream samples stored at -20°C, the reduction in H. pylori load was rapid at first, it was log4 and log3 in groups of 0.8% and 1.6% concentrations, respectively versus log5 in control samples. At the third day H. pylori was not able to be counted or isolated at third day of storage for both concentrations. Conclusion: All isolates recovered from small scale ice cream samples reflexing the hygienic conditions under which samples were produced. Mastic gum essential oil exhibited a powerful anti-H. pylori effect recommending its addition to food matrix for therapeutic purposes or as a functional food. http://doi.org/10.5455/javar.2017.d199 XML PubReader